Effectiveness of Health Education Role Play Method and Audio-Visual Methods of Skills First Aid Syncope Among Senior High-School Students - Berlian Yuli Saputri; Aesthetica Islamy; Anis Murniati (Universitas Airlangga, 2025)
Introduction: Delays and errors in providing first aid to victims experiencing syncope can significantly increase the risk of complications and even mortality. Syncope requires immediate, appropriate intervention, making first aid skills essential for students. This study aimed to compare the effectiveness of the roleplay method and the audiovisual method in improving students’ skills in providing first aid for syncope. Methods: This study employed a quasi-experimental design with a nonequivalent group posttest-only approach. The population consisted of all 442 students in Class X at SMAN 1 Kedungwaru, Tulungagung, Indonesia. Using purposive sampling with specific inclusion and exclusion criteria, 71 students were recruited. Participants were divided into two groups: the roleplay group (n = 35, Class X-1) and the audiovisual group (n = 36, Class X-2). The independent variable was the health education method, while the dependent variable was the level of syncope first aid skills. Data were collected using an observation checklist, with a Content Validity Index (CVI) of 0.86, confirming its validity. Data analysis was performed using the Mann–Whitney U test. Results: The demographic characteristics showed comparable distributions between groups. In the roleplay group, 49% (n = 17) of students demonstrated good skills, whereas in the audiovisual group, the majority 47% (n = 17) achieved only moderate skill levels. The Mann–Whitney test yielded a p-value of 0.001 (< 0.05), indicating a significant difference between the two methods. Conclusions: Roleplay is more effective than audiovisual because respondents have the opportunity to practice directly so they learn and see more clearly.